(untitled) (Journal on studies and research of academic knowledge, 2014)
The article analyzes the enterprise micro organizational characteristics to check if the differential features of the export behavior of Small and Medium Businesses establish possible relationships in the performance of these companies. It is a quantitative correlational research on a sample of firms the wood industry and manufacturing in Misiones, using the technique of descriptive statistics. The correlations of a specific set of internal characteristics of firms with the results or performance of the export related to export sales per firm is evaluated. The export performance would be linked to a business process maturity, as to the accumulation of knowledge and learning experience in productive activity and the development of the export business in the diversification of products and markets, and improvements to its process productive of investments and linkage activities that help to stay in international markets The positive correlation with the minimum size thresholds, experience and export intensity would confirm that firms require certain level of productiv capacity, resources and competitive advantages to commit themselves long-term paths.